Religion and sustainable development of Rongmei tribe in Manipur - Panmei Peter (Journal of Research and Multidisciplinary, 2023)
Religions role in development has generally been seen with doubtful, if there is no difference, in scholarly and institutional and concerns with development planning and policy. In this paper, I focus the religion-sustainable development which specifically, and analyses in quantitative and be considered in the sustainable development goal. In view of its vast and different adherents and its common belief in the dignity of the human person under God, religion is committed to the promotion of the human good so as to provide basic needs, guarantee protection of human rights and promote integral development of the society. Religion gives a unique influence on all societies and many of the world’s peoples. Throughout history, it has given to be the primary force for social progress, motivating individuals to develop spiritual qualities, and empowering them to sacrifice for their fellow human beings and to contribute to the betterment of their communities. In this paper, 162 individual comprising of 108 male 54 female were collected randomly. Age group is 36 from 35 to 45 age and 126 from age group of above 45. Out of this, 72 individuals were from “leadership in society or organization” and 126 from “none” category. The paper analyse through spss software using descriptive statistics and bivariate. The cut off value of cronbachs alpha is 0.5 mean is compared to cronbachs alpha. It is significant in study as mean cross the cut off value of alpha.